Fenomena Pedagang Kaki Lima dalam Sudut Pandang Kajian Filsafat Hukum dan Perlindungan Konsumen - Shidarta, Shidarta (Humaniora, 2014)
Street vending always becomes one of main problems in many big cities like Jakarta if the existence of street vendors is perceived as a burden and never comprehensively addressed. It is the main concern raised in this article . A more comprehensive perspective can be applied by using philosophical and legal approaches . This article provides two points of view in term of the phenomena, i.e. legal philosophy and consumer [legal] protection. The first relates the subject matter to the universal legal values known as the legal objectives. The second one includes two perspectives, i.e. the proctection for consumers of street vendor’s products and that for street vendor as consumer of [legal] public policy.